Evaluation of outcome of medical and surgical management in cesarean scar pregnancy in a tertiary health care institute of Northen India - Kaur, Harpreet; Aggarwal, Muskan; Kaur, Sarvjeet; Kaur, Jaspreet; Choudhary, Vinita; Kaur, Jyotsimran; Kaur, Gagandeep (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
A rare form of ectopic pregnancy known as caesarean scar pregnancy (CSP) is associated with high rates of morbidity and mortality. When a growing conceptus is pathologically implanted into the site of a prior caesarean section, CSP ensues. Transvaginal ultrasonography (TVS) and transabdominal ultrasound are the main diagnostic methods for CSP. It was a series of clinical cases diagnosed over a period of 1 year. The clinical characteristics included in the study were maternal age, gravidity, number of prior caesarean sections, number of abortions, interval between CSP and caesarean sections, gestational age, mean size of the residual gestational tissue before intervention, serum β-hCG levels before and after intervention. All cases were detected timely in the first trimester itself on USG evaluation. Amongst all cases, ß hCG levels at the time of admission varied between 266 mIU/ml-56,265 mIU/ml. 30% patients were treated with medical management only with inj. methotrexate and inj. folinic acid out of which 60% of cases had failed medical management and had to undergo further surgical procedure. 30% of cases with failed medical management were planned for hysteroscopic curettage, 20% underwent dilatation and curettage (D and C) while only 1 patient who was diagnosed with early placenta accreta required hysterectomy. CSP is a rare yet life threatening obstetric condition. Medical management should be used as the first line of treatment in patients with hemodynamic stability. Laparotomy and embolization are invasive procedures that should only be used in patients with failed medical management or patients with severe bleeding.